A technical report on the development of a real-time visual biofeedback system to optimize motor learning and movement deficit correction - Bonnette, S.; DiCesare, C. A.; Kiefer, A. W.; Riley, M. A.; Barber Foss, K. D.; Thomas, S.; Diekfuss, J. A.; Myer, G. D. (Journal of Sports Science & Medicine, 2020)
This technical report describes the design and implementation of a novel biofeedback system to reduce biomechanical risk factors associated with anterior cruciate ligament (ACL) injuries. The system provided objective real-time biofeedback driven by biomechanical variables associated with increased ACL injury risk without the need of a present expert. Eleven adolescent female athletes (age = 16.7 ± 1.34 yrs; height = 1.70 ± 0.05 m; weight = 62.20 ± 5.63 kg) from the same varsity high school volleyball team were enrolled in the experiment. Participants first completed 10 bodyweight squats in the absence of the biofeedback (pretest), 40 bodyweight squats while interacting with the biofeedback, and a final 10 bodyweight squats in the absence of the biofeedback (posttest). Participants also completed three pretest drop vertical jumps and three posttest drop vertical jumps. Results revealed significant improvements in squat performance, as quantified by a novel heat map analysis, from the pretest to the posttest. Additionally, participants displayed improvements in landing mechanics during the drop vertical jump. This study demonstrates that participants were able to interact effectively with the real-time biofeedback and that biomechanical improvements observed during squatting translated to a separate task. Key Points